Efficacy and safety of CalliSpheres drug-eluting beads for bronchial arterial chemoembolization for refractory non-small-cell lung cancer and its impact on quality of life: A multicenter prospective study - Zhao, Yu Wei; Liu, Song; Qin, Hao; Sun, Jin Bo; Su, Mao; Yu, Guang Ji; Zhou, Jun; Gao, Fei; Wang, Ruo Yu; Zhao, Tong; Zhao, Guang Sheng (Frontiers in Oncology, 2023)
Objective: This study aimed to prospectively observe the efficacy and safety of CalliSpheres drug-eluting beads bronchial arterial chemoembolization (DEB-BACE) for refractory non-small-cell lung cancer (NSCLC). Methods: The interventional therapy plan was as follows: 300–500 μm CalliSpheres drug-loaded microspheres were loaded with epirubicin, and then slow embolization of tumor supplying artery was performed after microcatheter superselection. Chest enhanced computed tomography and related hematological examination were reviewed after 2 months of DEB-BACE, and the tumor response after the first interventional therapy was evaluated using modified response evaluation criteria in solid tumors. The overall survival (OS) of patients was determined, and the quality of life and the incidence rate of adverse reactions were observed. Results: From January 2019 to January 2021, 43 patients with refractory NSCLC were enrolled. The patients were followed up until June 2022. All 43 patients underwent DEB-BACE 1.79 ± 0.69 times on average. The 3-, 6-, 12-, and 24-month survival rates were 100%, 86.0%, 41.9%, and 11.8%, respectively. The median OS was 11.5 months. After the first interventional treatment, cough and wheezing significantly improved in 31 patients, hemoptysis was effectively controlled in 12 patients, and superior vena cava compression disappeared in 2 patients after 2 times of treatment. The general health status of the patients after treatment significantly improved compared with that before treatment, including the improvement in physical and emotional functions. Fatigue, nausea and vomiting, dyspnea, and insomnia improved significantly after treatment. No serious adverse events, such as spinal cord injury and cerebral embolism, were observed during the perioperative period. The main adverse reaction after DEB-BACE was chest pain (13/43, grade 1) followed by fever (10/43, grade 1–2), which was significantly relieved within 3–5 days after symptomatic treatment. Other adverse reactions included irritating cough, nausea and vomiting, and bone marrow suppression, and the incidence was less than 20%. Conclusions: DEB-BACE was effective and safe in treating refractory NSCLC, which could significantly improve patients’ quality of life and was worthy of clinical promotion and application.